(untitled) (Connessioni remote. Artivismo_Teatro_Tecnologia, 2021)
This paper analyses salient debates in the history of critical thinking related to participatory practices in a number of disciplines and fields, including art, theatre, development, architecture, broadcasting and science. Participation, the author maintains, is not only a form of empowerment and knowledge generation, identity and community creation, it is also a type of economy which facilitates self- production, privileges social connection (or relationships) over consumption or possibly turns social connection in a new form of consumption.